A two years study on vectors of cutaneous leishmaniasis: Evidence for sylvatic transmission cycle in the State of Campeche, Mexico - Eduardo A Rebollar-Téllez; Alejandro Ramírez-Fraire; Fernando J Andrade-Narvaez (Memorias do Instituto Oswaldo Cruz, 1996)
Vectors of cutaneous leishmaniasis in the State of Campeche were studied in relation to the transmission cycle of Leishmania (Le.) mexicana. To determine how transmission of leishmaniasis occurs, we collected phlebotomine sand flies for two years. In the first year (October 1990 to November 1991) the collections were made with CDC light traps, Shannon traps and direct captures at natural shelters around the village (<200 m) of La Libertad. In the second year (February 1993 to January 1994) the catches were performed at 8 km southeast of La Libertad in the forest. Female sand flies were examined for Leishmania. During the first year, 347 sand flies of nine species were collected, most of which were Lutzomyia deleoni (61.3%). When all nine species were considered, more females than males were captured. Low densities of anthropophillic species of sand flies around the village indicated that sylvatic transmission was taking place. For the second year, 1484 sand flies of 16 species were caught. The most common were L. olmeca olmeca (21.7%), L. cruciata (19.2%) and L. ovallesi (14.1%). Similarly, more females were caught than males. Thirty-five females of five species were found infected with flagellates believed to be Leishmania sp. The highest infection rate was found in L. olmeca olmeca (7.1%) followed by L. cruciata (4.5%) and L. ovallesi (1.1%). These data plus other evidence on the epidemiology of human cases and results from reservoir studies are discussed in relation to the sylvatic transmission cycle.